Implementation of Merdeka Curriculum: P5 Theme Build the Soul and Body Using Project-Based Learning - Setyawati, Nanik; Mulyanah, Mulyanah; Pamuningtyas, Astrilina; Arda Nugroho, Suryo Prakoso; Firdaus, Firdaus (ISTIFHAM, 2025)
This research aims to analyze the implementation of the Merdeka Curriculum in the context of the Pancasila Student Profile Strengthening Project (P5) with the theme "Build the Soul and Body." The main focus of this research is to explore how applying this theme in the curriculum can affect students' character-building and competency development. This research also explores the effectiveness of applying the Project Based Learning (PjBL) model in implementing the P5 project. Using the PjBL model allows students to develop creativity and independence because they can process ideas and carry out various project activities independently. The research method used was qualitative with a descriptive approach. Data was collected through observation, interviews, discussions, and direct field research. The data were analyzed using a qualitative descriptive approach, which is expected to provide valuable insights for curriculum development that is more relevant to future educational needs and contribute to the understanding of strengthening the learner profile of Pancasila through a project-based learning approach. The implementation results show that learners can understand the importance of maintaining mental and physical health and develop 21st-century skills, such as critical thinking, creativity, communication, and collaboration. These findings suggest that integrating PjBL in the Merdeka Curriculum can be an effective strategy for building learner competencies following the values of the Pancasila Learner Profile.